Powerless in the Virgin Islands: Emergency Department and Wound Care Clinic Utilization Following the 2017 Hurricanes Irma and Maria on St. Thomas, U.S. Virgin Islands. (22nd October 2023) - Christopher, Kenneth E; Kitsantas, Panagiota; Farrell-Sealey, Sherla; Hunte-Ceasar, Tai
Abstract: Objective: The main objective of this work was to characterize the prevalence of acute medical needs by examining emergency department (ED) and outpatient wound care clinic (WCC) visits before, during, and after the 2017 Hurricanes Irma and Maria, in St. Thomas, United States (U.S.) Virgin Islands. Methods: Descriptive statistics and logistic regression were used to assess associations between the occurrence of the storms and visits due to injuries and chronic conditions presented to the ED and WCC from September 1, 2016 to May 31, 2018. Results: ED visits increased and the rate of injury care was higher during the storms (12 patient visits per day) than before or after the storms (9 patient visits per day). WCC visits increased during (12%) and after the storms (45%), and were associated with patients 60 years and older. The odds of ED and WCC visits due to injury during the storms were significantly higher (odds ratio [OR]: 1.28, 95% confidence interval [CI]: 1.17, 1.40) than prior to the storms. The odds for visits due to injuries were 1.19 (95% CI: 1.12, 1.28) times higher after the storms. Conclusions: Increases occurred in ED and WCC visits for injury care during the storms and in WCC visits after the storms. Public health preparedness mandates understanding how major hurricanes impact the prevalence of acute medical needs, and the factors that influence decisions to seek medical care, in their wake.